Comparative QSAR studies using HQSAR, CoMFA, and CoMSIA methods on cyclic sulfone hydroxyethylamines as BACE1 inhibitors. (April 2017) - Zhang, Shuqun; Lin, Zichun; Pu, Yinglan; Zhang, Yunqin; Zhang, Li; Zuo, Zhili
Graphical abstract: Highlights: Three HQSAR, CoMFA and CoMSIA methodologies were used in this study. CoMSIA model shows the best correlation and satisfactory predictability. QSAR models yield key structural modification information to improve bioactivity. Further understanding of the vital interactions between receptor and ligands. Abstract: The inhibition of β-secretase (BACE1) is currently the main pharmacological strategy available for Alzheimer's disease (AD). 2D QSAR and 3D QSAR analysis on some cyclic sulfone hydroxyethylamines inhibitors against β-secretase (IC50 : 0.002–2.75 μM) were carried out using hologram QSAR (HQSAR), comparative molecular field analysis (CoMFA), and comparative molecular similarity indices analysis (CoMSIA) methods. The best model based on the training set was generated with a HQSAR q 2 value of 0.693 and r 2 value of 0.981; a CoMFA q 2 value of 0.534 and r 2 value of 0.913; and a CoMSIA q 2 value of 0.512 and r 2 value of 0.973. In order to gain further understand of the vital interactions between cyclic sulfone hydroxyethylamines and the protease, the analysis was performed by combining the CoMFA and CoMSIA field distributions with the active sites of the BACE1. The final QSAR models could be helpful in the design and development of novel active BACE1 inhibitors.